MANAJEMEN KARIR SEBAGAI STRATEGI PENGEMBANGAN SDM : DALAM PERENCANAAN KARIR DI ERA REVOLUSI INDUSTRI 4.0 MENUJU SOCITY 5.0 - Ramadhan, Ryan Maulana; Triwanda, Desy; Wijaya, Fadilah Rizka; Mardiyah, Mardiyah (STKIP Pesisir Selatan, 2025)
This study aims to analyze career management as a strategy for human resource (HR) development in the context of the Industrial Revolution 4.0 and the transition toward Society 5.0, focusing on the implications and challenges faced by Tarbiyah students as prospective educators. The research employed a qualitative approach through a literature review, complemented by in-depth interviews with students actively engaged in academic and non-academic activities. The findings reveal that career management involves planning, developing, and managing career paths through strategies such as training, mentoring, internships, as well as strengthening soft skills and digital literacy. Results indicate that Tarbiyah students tend to integrate Islamic values, employability skills, and digital competencies in their career planning. However, challenges such as limited access to advanced technology, lack of digital-based career guidance, and competency mismatches with industry needs remain significant obstacles. The novelty of this study lies in the integration of spiritual, professional, and digital aspects within students’ career strategies, emphasizing the crucial role of higher education institutions in providing adaptive curricula, career center services, and relevant experiential learning opportunities.